Quantitative Analysis: Capital Structure, Company Size And Liquidity On Financial Performance At PT. Bank Artha Graha Internasional Tbk In 2014-2024 - Gina Hermalianti; Rita Tri Yusnita; Selji Salgangga (Utami Publisher, 2026)
This study aims to analyze the influence of Capital Structure, Company Size, and Liquidity on the Financial Performance of PT Bank Artha Graha Internasional Tbk for the 2014-2024 period. Financial performance is measured by the Return on Assets (ROA), Capital Structure by the Debt to Equity Ratio (DER), Company Size by Size = Ln, and Liquidity by the Loan to Deposit Ratio (LDR). The study used an associative quantitative method with secondary data from annual and sustainability reports. A sample of 44 companies was selected through purposive sampling. The analysis was conducted using the classical assumption test and multiple linear regression. Based on the results of the F test it shows that capital structure, company size, and liquidity simultaneously have a significant effect on financial performance. Based on the results of the T test it shows that capital structure has a significant positive effect on financial performance. Company size has a significant negative effect on financial performance. Liquidity has no a significant effect on financial performance.